Effect of color feature normalization on segmentation of color images - Khan, J. (Institute of Electrical and Electronics Engineers Inc., 2017)
The segmentation of acne vulgaris lesions is a crucial step for the classification and developing a severity assessment system. In this paper, an unsupervised technique is proposed for the segmentation of acne vulgaris lesions. The effect of color feature normalization on segmentation results is examined. Two types of normalization is performed-in the first type, the color feature values are restricted to the range 0 1 and in the second type, the color features are normalized such that their mean value is zero and their variance is one. The segmentation of acne lesions was carried out in the feature set formed by combining chromatic components from different color spaces such as YIQ, Lab, I1I2I3 and YCbCr. A dataset of fifty color images of acne patients have been used in this experimentation. The segmentation results show that normalization can significantly improve the segmentation results in YIQ and I1I2I3 color spaces. It has also found that comparatively good segmentation results can be obtained in high dimensional chromatic space. © 2016 IEEE.